The Chelyabinsk meteorite: thermal history and variable shock effects recorded by the 40Ar-39Ar system - Trieloff, Mario; Korochantseva, Ekaterina V.; Buikin, Alexei I.; Hopp, Jens (Meteoritics & planetary science, 2018)
We studied three lithologies (light and dark chondritic and impact melt rock) differing in shock stage from the LL5 chondrite Chelyabinsk. Using the 40Ar-39Ar dating technique, we identified low- and high-temperature reservoirs within all samples, ascribed to K-bearing oligoclase feldspar and shock-induced jadeite-feldspar glass assemblages in melt veins, respectively. Trapped argon components had variable 40Ar/36Ar ratios even within low- and high-temperature reservoirs of individual samples. Correcting for trapped argon revealed a lithology-specific response of the K-Ar system to shock metamorphism, thereby defining two distinct impact events affecting the Chelyabinsk parent asteroid (1) an intense impact event 1.7 ± 0.1 Ga ago formed the light-dark-structured and impact-veined Chelyabinsk breccia. Such a one-stage breccia formation is consistent with petrological observations and was recorded by the strongly shocked lithologies (dark and impact melt) where a significant fraction of oligoclase feldspar was transformed into jadeite and feldspathic glass; and (2) a young reset event 30 Ma ago particularly affected the light lithology due to its low argon retentivity, while the more retentive shock-induced phases were more resistant against thermal reset. Trapped argon with 40Ar/36Ar ratios up to 1900 was likely incorporated during impact-induced events on the parent body, and mixed with terrestrial atmospheric argon contamination. Had it not been identified via isochrons based on high-resolution argon extraction, several geochronologically meaningless ages would have been deduced.